Flexible microwave absorber based on nickel ferrite nanocomposite - Sunny, Vijutha; Kurian, Philip; Mohanan, P.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2010)
Flexible magnetic composite materials were prepared by incorporating precharacterized nickel ferrite nanoparticles in a natural rubber matrix. The complex dielectric permittivity and magnetic permeability of the composites were measured at different microwave frequencies using the cavity perturbation technique. A steady increase in dielectric permittivity was observed with increase in filler concentration. Maxwell-Garnett mixture equations were employed to model the effective permittivity and permeability of the composite. Reflection loss was estimated by employing the model of single layer absorber backed with a perfect conductor. Reflection loss minima of -5.9 dB at 3.2 GHz for 12 mm thick rubber ferrite composite sheet is obtained in the S-band while a loss up to -16 dB could be achieved at 9.5 GHz in the X-band. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cavity perturbation; Complex permeability; Complex permittivity; Microwave absorber; Nanocomposites; Nickel ferrite

Flexible microwave absorbers based on barium hexaferrite, carbon black, and nitrile rubber for 2-12 GHz applications - Vinayasree, S.; Soloman, M. A.; Sunny, Vijutha; Mohanan, P.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Applied Physics, 2014)
Flexile single layer electromagnetic wave absorbers were designed by incorporating appropriate amounts of carbon black in a nitrile butadiene rubber matrix along with an optimized amount of magnetic counterpart, namely, barium hexaferrite for applications in S, C, and X-bands. Effective dielectric permittivity and magnetic permeability were measured using cavity perturbation method in the frequency range of 2-12 GHz. The microwave absorbing characteristics of the composites were studied in the S, C, and X-bands employing a model in which an electromagnetic wave is incident normally on a metal terminated single layer. Reflection loss exceeding -20 dB is obtained for all the samples in a wide frequency range of 2-12 GHz when an appropriate absorber thickness between 5 and 9 mm is chosen. The impact of carbon black is clearly observed in the optimized composites on the mechanical strength, thickness, band width of absorption, dielectric properties, and absorptivity. (C) 2014 AIP Publishing LLC.